A New Record of the Pseudolaguvia nubila (Siluriformes: Erethistidae) from Baandhkhola (Stream) in Central Nepal - Rayamajhi, Asha; Arunachalam, M. (International Journal of Applied Sciences and Biotechnology, 2017)
In this study, we describe a miniature sisorid catfish of the family Erethistidae, as a new distributional record of Pseudolaguvia nubila from the Baandhkhola (stream), a tributary of Narayani River inCentral Nepal. Pseudolaguvia nubila shows its distribution to Nepal is distinguished from its congeners by combination of characters, such as- two broad and distinct yellowish vertical bands at the origin of dorsal fin and anal fin, smooth outer edge of the dorsal fin spine, dorsal fin spine length 13.23-17.60 % SL, pectoral fin length 24.89-26.27 % SL, pectoral fin spine length 18.39-19.48 % SL and body depth at anus 17.22-18.69 % SL.Int. J. Appl. Sci. Biotechnol. Vol 5(4): 434-441